A,The IMPLEMENTING MULTIPLE INTELLIGENCE TO IMPROVE THE SPEAKING ABILITY OF SMP NEGERI 3 DUAMPANUA - Mulu, Muliani (La Parole : Journal of Language Teaching and Pedagogy, 2021)
ABSTRACT The major problems of this research were how to enhance the students’ speaking ability. Then how to motivate the students to speak in English so this research conducted to find out whether implementing Multiple Intelligence effective to improve the students’ speaking of SMP Negeri 3 Duampanua. A quasi-experimental method was carried out by researcher in this research. The population of SMP Negeri 3 Duampanua. VIII.1 and VIII.2 were taken as sample. The instruments that used in collecting the data were interview test and questionnaire. The result of the research shows the students’ speaking ability of the experimental was better than the control group. It was proved by the data of the students’ mean score on experimental class was higher tha the control group (69.16 ˃ 60.52). Futhermore, implementing multiple intelligence improve the student speaking ability. Besides, the research finding also shows the students interest toward the implementing of this simulation. Keywords: Multiple intelligence, Students’ interest, Speaking ability ABSTRAK Masalah utama dari penelitian ini adalah bagaimana meningkatkan kemampuan berbicara siswa. Lalu bagaimana memotivasi siwa untuk berbicara bahasa Inggris sehingga penelitian ini dilakukan untuk mengetahui apakah penerapan kecerdasan ganda efektif untuk meningkatkan kemampuan berbicara SMP Negeri 3 Duampanua. Metode kuasi eksperimen dilakukan oleh peneliti dalam penelitian ini. Populasi penelitian ini adalah SMP Negeri 3 Duampanua. VIII.I dan VIII.2 diambil sebagai sampel. Instrumen yang digunakan dalam mengumpulkan data adalah tes wawancara dan kuesioner. Hasil penelitian menunjukkan kemampuan berbicara siswa kelas eksperimen lebih baik daripada kelompok kelas kontrol. Itu dibuktikan dengan data skor rat-rata siswa di kelas eksperimen lebih tinggi daripada kelompok kelas kontrol (69.16 ˃ 60.52). selain itu penerapan kecerdasan ganda meningkatkan kemampuan berbicara siswa. Selain itu, temuan penelitian ini juga menunjukkan minat siswa terhadap penerapan simulasi ini. Ini dibuktikan ole data dari kuesioner dimana minat siswa adalah yang dikategorikan sangat setuju. Kata kunci: kecerdasan ganda, minat siswa, kemampuan berbicara.